PERBANDINGAN KADAR GLUKOSA DARAH YANG DIPERIKSA SEGERA, DITUNDA 1 JAM DAN 2 JAM MENGGUNAKAN METODE GOD-PAP PADA PASIEN DIABETES MELLITUS DI PUSKESMAS CEMPAKA - Hidriya, Hajrah; Aswandi, Aswandi; Hilalliyah, Nur; Ripani, Ahmad (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
Cempaka Central Banjarmasin community health center is a community health center that has a strategic location, in the middle of Banjarmasin City. There are more or less than 23 patients in 1 day doing blood glucose examination and about more than 5 patients had a history of Diabetes Mellitus in the laboratory. Thus the laboratory does not conduct specimen examination immediately because of the limited number of laboratory personnel. Meanwhile it also has limited equipment and not yet fully automatic. This study aims to determine whether or not there is a Difference of Blood Glucose Levels that are Checked Immediately, Postponed 1 Hour and 2 Hours Using the GOD-PAP Method in Diabetes Mellitus Patients in Cempaka Public Health Center, Central Banjarmasin, using an experimental observation method. The independent variable of this study was the measurement of blood glucose levels which were examined immediately, postponed 1 hour and 2 hours and the dependent variable of this study was the blood glucose level. The sampling technique used purposive sampling, by examining the serum specimens of patients with a history of Diabetes Mellitus by 10 samples. Based on the results of the examination of blood glucose levels that were immediately examined, postponed 1 hour and 2 hours there was a significant difference between groups with the Friedman test with a significant Chi-Square Count> Chi-Square Table (20,000> 5,991) and a significant P-value 0,000 <0.05 and Post Hoc test with a significant value of P-value 0.005 <α (0.05). Based on the results of the research conducted there were significant differences in the immediate examination with a delay of 1 hour and 2 hours.